Valoración económica del servicio ambiental hídrico en el páramo de Pastocalle, cantón Latacunga, provincia de Cotopaxi, 2018. - Pillo Arequipa, Tania Yadira (2018)
The present investigation was carried out with the objective to determine the economic value of the water environmental service of the San Juan de Pastocalle highlands, it was carried out on three stages: determination of the geographical and physical conditions of the area under study, by highlands georeference and secondary information in shapefile format for the variables: hydrographic units, slope, potential land use and vegetation cover. In the second stage, the hydrological study, water balance to determine the total water supply and the available water supply of the Pastocalle highlands, to calculate precipitation, temperature, evapotranspiration and the opportunity cost obtained through producers surveys, data systematized in the software R. On the third stage the availability of water users administration boards was calculated. The total water supply of the area under study is 36 509 412 m3 year-1, of this supply 43% is lost by evapotranspiration, and 20 975 714 m3 year-1 of available water supply, However, 18% of this Water is already being used by 40 management boards for different uses. The average calculation of the opportunity cost is 3155 USD, according to the obtained results, the total water productivity value of the highlands was determined. The annual value per hectare is USD 262.8, the monthly value per hectare is USD 55.2, which is equivalent to a value of 0.07 dollars per m3 of water. As one of the alternatives it is considered that the water management boards buy the highlands or in turn the autonomous governments in conjunction with the MAG, ONGs and the MAE finance the boards for environmental and productive projects for conservation, protection and recovery of the highlands ecosystem and its water sources.